SAT0279 Tocilizumab in Refractory Aortitis: Study on 16 Patients and Literature Review. (10th June 2014) - Loricera, J.; Blanco, R.; Castañeda, S.; Humbría, A.; Ortego-Centeno, N.; Narváez, J.; Mata, C.; Melchor, S.; Aurrecoechea, E.; Calvo-Alén, J.; Lluch, P.; Moll, C.; et al.
Abstract : Background: Non-infectious aortitis is often refractory to standard immunosuppressive therapy. IL-6 has been implicated in the pathogenesis of aortitis. Objectives: Our aim was to assess the efficacy of the anti-IL6 receptor monoconal antibody tocilizumab (TCZ) in a series of patients with refractory non-infectious aortitis. Methods: We reviewed 16 patients (14 women/2 men) with refractory aortitis diagnosed by imaging (CT angiography, MR angiography, and/or PET) that were treated with TCZ. Results: The mean age ± SD was 51.4±20.1 years. The underlying conditions were: Takayasu arteritis (TakA) (N=7 cases), giant cell arteritis (GCA) (n=7), relapsing polychondritis (RP) (n=1), and aortitis associated with retroperitoneal fibrosis (n=1). TCZ was the first biologic drug used in all patients with GCA, and in the patient with aortitis associated with retroperitoneal fibrosis but in only 2 of 7 TakA patients. In the remaining cases anti-TNF inhibitors were prescribed before TCZ (standard dose was 8 mg/kg/iv/4 weeks). After a mean ± SD follow-up of 11.8±6.6 months most patients experienced clinical improvement, showing reduction of erythrocyte sedimentation rate from 43±36 mm/1st h to 5±4 mm/1st h at last visit. At TCZ onset, 25% of patients had fever and 19% polymyalgia rheumatica. These manifestations disappeared after 3 months of TCZ therapy. A corticosteroid sparing effect was also achieved (from 27.3±17.6 mg/day of prednisone at TCZ onset to 4.2±3.8 mg/day at last visit). TCZ had to be discontinued in a patient because of severe neutropenia. Conclusions: TCZ appears to be effective and relatively safe in patients with inflammatory aortitis refractory to corticosteroids or to other biologic immunosuppressive drugs. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2984